The preventable efficacy of β-glucan against leptospirosis. - Jiaqi Wang; Zhao Jin; Wenlong Zhang; Xufeng Xie; Ning Song; Tianbao Lv; Dianjun Wu; Yongguo Cao (Public Library of Science (PLoS), 2019)
Leptospirosis, caused by pathogenic Leptospira species, has emerged as an important neglected zoonotic disease. Few studies have reported the preventable effects of immunoregulators, except for antibiotics, against leptospirosis. Generally, immunostimulatory agents are considered effective for enhancing innate immune responses. Many studies have found that beta-glucan (β-glucan) could be a potent and valuable immunostimulant for improving immune responses and controlling diseases. In this study, we investigated the preventable role of β-glucan against Leptospira infection in hamsters. First, β-glucan was administered 24 h prior to, during and after infection. The results showed that β-glucan increased the survival rate to 100%, alleviated tissue injury, and decreased leptospire loads in target organs. Additionally, we found using quantitative real-time PCR that application of β-glucan significantly enhanced the expression of Toll-like receptor (TLR) 2, interleukin (IL)-1β and iNOS at 2 dpi (days post infection) and reduced the increase of TLR2, IL-1β and iNOS induced by Leptospira at 5 dpi. Furthermore, to induce memory immunity, β-glucan was administered 5 days prior to infection. β-Glucan also significantly increased the survival rates and ameliorated pathological damage to organs. Moreover, we demonstrated that β-glucan-trained macrophages exhibited elevated expression of proinflammatory cytokines (IL-1β and IL-6) in vitro, indicating that β-glucan induces an enhanced inflammatory response against Leptospira infection. These results indicate that administration of β-glucan and other immunostimulants could be potential valuable options for the control of Leptospira infection.